TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK ADOPSI ANAK DI GAMPONG TANOH ANOU KECAMATAN IDI RAYEUK KABUPATEN ACEH TIMUR - T. Wahyu Srimuryadi (Hukum Keluarga Islam IAIN LANGSA, 2018)
Adoption on the initial basis is the adoption of a child that results in the adoption of anadopted child from his own father's relationship and is included in the relationship of his adoptivefather. In practice adoption is usually carried out by people who in their marriages do not produceoffspring. By adopting the adopted child has a relationship with the adoptive father as with his ownfather. Inherited inherited relationship between adopted children and adoptive father. Before Islamcame, adoption had been carried out by Arabs and had become a hereditary tradition known astabanni which means taking children. Or take someone else's child to be given the status of abiological child, so that he has the right to use the nasab of his adoptive parents and has the right toinherit inheritance and other rights as a relationship between children and parents.